LEARNING ABOUT HEALTHY HABITS AMONG PRIMARY SCHOOL STUDENTS IN NORTH OF LIMA - Yovera, Elizabeth (2020)
Objectives: To evaluate and compare the level of learning about healthy habits through audiovisual media and text in primary school students. Materials and methods: Quasi-experimental study carried out in two Primary Educational Institutions located in North of Lima. Students of both sexes between 10 and 12 years of age who were in the fourth, fifth and sixth grade voluntarily participated. The study variable was the level of learning about healthy habits (healthy food and physical activity) after an educational session by trained personnel, applied in two intervention groups, in the first group a text was used and in the second group a medium audiovisual. The measurement was made with an evaluation questionnaire applied to both groups. Results: In the post-test, the group of children who participated with text reading obtained a mean score of 64.68 (95% CI: 61.03 to 68.32), while in the group evaluated after the video display the mean score was of 64.73 (95% CI: 61.70 to 67.77). There were no differences in the median post-test scores between the text and video group (p = 0.949). Conclusion: Texts and audiovisual materials had a similar effect on the level of learning about healthy habits.